Changes in Mortality According to Creatinine/Cystatin C Ratio in Chronic Kidney Disease and Non-chronic Kidney Disease Patients - Hwang, Jeong Ah; Song, Younghoon; Shin, Jaeun; Cho, Eunjung; Ahn, Shin Young; Ko, Gang Jee; Kwon, Young Joo; Kim, Ji Eun (Frontiers in Medicine, 2022)
Background: Serum creatinine and cystatin C are not only good indicators of renal function but have also been confirmed to be related to disease prognosis and mortality in various diseases via creatinine/cystatin C ratio (CCR). However, although they are biomarkers of renal function, there is no study regarding renal impairment as a confounding variable in the relationship between CCR and all-cause mortality. Methods: Patients who had simultaneous measurements of serum creatinine and cystatin C between 2003 and 2020 were enrolled. The patients with chronic kidney disease (CKD) were defined as having an estimated glomerular filtration rate (eGFR) CKD-EPI Cr-Cystatin C < 60ml/min/1.73m2. CCR was calculated by dividing the serum creatinine level by the cystatin C level measured on the same day. The main outcome assessed was all-cause mortality according to CCR in CKD or non-CKD groups. Results: Among the 8680 patients in whom creatinine and cystatin C levels were measured simultaneously, 4301 were included in the CKD group, and 4379 were included in the non-CKD group, respectively. CCR was 1.4±0.6 in total participants. The non-CKD group showed higher mean CCR, (1.5±0.7 vs. 1.3±0.5) as well as a wider distribution of CCR (p < 0.001) when compared to the CKD group. In non-CKD group, 1st, 4th and 5th quintiles of CCR significantly increased the all-cause mortality risk compared to 2nd quintile of CCR, suggesting U-shaped mortality risk according to CCR in non-CKD. On the other hand, in CKD group, the risk of all-cause mortality linearly increased and 5th quintile of CCR showed 1.82 times risk of mortality compared to 2nd quintile of CCR. In the subgroup analysis of mortality by age and sex, the mortality difference according to CCR were diminished in old age and female sex subgroups. Conclusion: We discovered a U-shaped relationship between mortality and CCR levels in normal renal function, and an increased risk of mortality in CKD with elevated CCR.